Developing Google Sites-Based E-Modules to Enhance Teachers’ ICT Competence at Al Husna Foundation - Ilma Fauziana Fariz; Sholeh Hidayat; Isti Rusdiyani (STAI Hubbulwathan Duri, 2025)
Integrating Information and Communication Technology (ICT) into teaching remains a significant challenge for many educators, particularly those at Yayasan Al Husna, Tangerang, who continue to rely on traditional methods despite available digital tools. Enhancing teachers’ ICT competence is essential to support more effective and engaging learning experiences. This study aimed to develop a Google Sites-based e-module to improve teachers' abilities in creating interactive, web-based instructional materials. The research employed the ADDIE instructional design model (Analysis, Design, Development, Implementation, and Evaluation) and adopted a mixed-methods approach. Data were collected through structured interviews, expert validations, questionnaires, and pre-post tests. Expert validation results showed a feasibility rating of 70% from a content expert and 92% from a media expert, classifying the e-module as